Pasture weed biology and management in Brazil - Martins, Dagoberto [UNESP]; Marchi, Sidnei Roberto de; Marques, Ricardo Fagundes [UNESP] (Univ Estadual Londrina, 2022)
The livestock production model historically practiced in Brazil has a strong extractive bias, wherein the premise is to produce livestock with absolutely no concern for the preservation or renewal of environmental resources. The absence of technical criteria for the use of pastures has generated low productivity rates, making the activity unsustainable from both economic and environmental points of view. This scenario led the several sectors linked to the production chain to develop a package of strategies to solve the problems faced by livestock farmers. This package of strategies is conventionally called postmodern or corporate farming, in which the extractive process gives way to the business logic of avoiding waste and recovering profit margins mainly through pasture perpetuation. However, there is still a technical gap in corporate cattle farming related to problems caused by pasture weeds because all the concepts applied are derived or copied from concepts generated in agriculture. Furthermore, few researchers have studied or scientific articles written on elucidating the real problem of weeds in livestock production. Thus, the goal of the present review was to present some aspects related to weed ecology, their interference, and management alternatives in pasture areas, thereby collaborating with corporate livestock farming in Brazil because solutions to weed problems are crucial to increase commitment in all sectors of the production chain.
Keywords: Control methods; Forage; Phytosociological indices; Weed interference